The propagation of hydraulic fracture in layered coal seam: a numerical simulation considering the interface thickness based on the distinct element method - Gao, Hongye; Jia, Baoshan; Lei, Yun; Zheng, Yongxiang; Shi, Bin; Wei, Haiyang; Zhang, Tongjing; Wang, Wei; Niu, Qinghe (Frontiers in Energy Research, 2024)
The intercalated layer of coal seam plays an important role in the propagation of hydraulic fracturing. To understand the role of the intercalated layer, a composite coal seam model considering the thickness of the intercalated layer was established. Based on the block distinct element method, the effects of rock structure (thickness of the coal seam and intercalated layer), rock properties (elastic modulus), and construction parameters (injection rate and fluid viscosity) on the penetration behavior of hydraulic fractures were analyzed. The results show that the intercalated layers influence the fracture deflection and have a hindering effect on fracture propagation. The thickness of the intercalated layer affects the stress on the bedding plane and the front edge of the fractures. On the contrary, the thickness of the coal seam mainly affects the penetration ability of hydraulic fractures and the extent of hydraulic fracture propagation. In addition, the elastic modulus of the intercalated layers and coal seams affects the hindering effect of the intercalated layer. The high injection rates reduce the hindering effect of the intercalated layer. When fracturing with a high-viscosity fluid, fractures are more likely to enter the intercalated layer. However, excessively high viscosity can make it difficult for fractures to penetrate the intercalated layer. This study can provide theoretical guidance for the fracturing of composite coal seams.